The Saccharomyces cerevisiae chitinase, encoded by the CTS1-2 gene, as an antifungal and biocontrol agent - Carstens, Maryke,1976- (Stellenbosch : Stellenbosch University, 2012)
Thesis (MScAgric) -- University of Stellenbosch, 2002.